Y+6=3(x-2)

Simple and best practice solution for Y+6=3(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y+6=3(x-2) equation:


Simplifying
Y + 6 = 3(x + -2)

Reorder the terms:
6 + Y = 3(x + -2)

Reorder the terms:
6 + Y = 3(-2 + x)
6 + Y = (-2 * 3 + x * 3)
6 + Y = (-6 + 3x)

Solving
6 + Y = -6 + 3x

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + Y = -6 + -6 + 3x

Combine like terms: 6 + -6 = 0
0 + Y = -6 + -6 + 3x
Y = -6 + -6 + 3x

Combine like terms: -6 + -6 = -12
Y = -12 + 3x

Simplifying
Y = -12 + 3x

See similar equations:

| 8.7n+4.5-3.2n=375 | | 3y+7=x-13 | | P=$1440/4 | | 3(2y+1)-5(12y-7)+(6y-1)=37 | | P=$1440/5 | | 13.2=t4.4 | | -4r-9=-14-3r | | x+4+3x=31 | | -2x-17=13-4x | | 4s^2=-36 | | -2Xx=5 | | 12-9x+45=-1+x | | R+25=9 | | 3x+1+4x=7x-3 | | 5d=9/10 | | 6x-17=13-4x | | 27.50x+23.25x=17 | | -9b=153 | | 28=4+11 | | (8x+1)(x-7)=(2x-3)(4x+5) | | 5(z+1)=4(z-8)+z | | 2q+58=-2+-4q | | y=-2cos(x) | | -2q+58=2+-4q | | (3/4×).(y/3) | | R/8=9 | | 1/2(4x=6)=0 | | -4x+.5y=1 | | 4a-4=8+2 | | x-32=-4x+23 | | x^3-9x^2+72x-260=0 | | 8m-6+8(m+2)=8m+42 |

Equations solver categories